2019
DOI: 10.1038/s41433-019-0456-5
|View full text |Cite
|
Sign up to set email alerts
|

An update on chemical eye burns

Abstract: Ocular chemical injuries vary in severity, with the more severe end of the spectrum having profound visual consequences and medicolegal implications. Grading of ocular injuries is critical for determining acute treatment and visual prognosis. Poor immediate management results in more challenging treatment of acute disease. Similarly, poorly controlled acute disease results in more treatment-resistant chronic ocular disease. Despite several decades of research and public health initiatives, simple and effective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
51
0
11

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(77 citation statements)
references
References 101 publications
2
51
0
11
Order By: Relevance
“…Men aged 18-64 years [4,10] and children aged 1-2 years [7,15] might be at the highest risk for ocular chemical injury in the workplace or residential locations due to occupational exposure and topical personal products and cleaning agents. In our study, the majority of the patients were factory workers and construction workers, which was in agreement with the findings of Bizrah and co-workers [16]: most ocular chemical injuries were work-related. Although the delay in the presentation of 133 (83.1%) patients for medical treatment was less than 24 h after injury, only 64 (40.0%) patients were at the consultation room in less than 3 h. Bizrah et al [14] also found that 87% of patients presented to the Moorfields Eye Hospital emergency department within 24 h, but they did not state the numbers of patients in more detailed time window (e.g., less than 3 h, within 3-6 h, within 6-12 h).…”
Section: Discussionsupporting
confidence: 93%
“…Men aged 18-64 years [4,10] and children aged 1-2 years [7,15] might be at the highest risk for ocular chemical injury in the workplace or residential locations due to occupational exposure and topical personal products and cleaning agents. In our study, the majority of the patients were factory workers and construction workers, which was in agreement with the findings of Bizrah and co-workers [16]: most ocular chemical injuries were work-related. Although the delay in the presentation of 133 (83.1%) patients for medical treatment was less than 24 h after injury, only 64 (40.0%) patients were at the consultation room in less than 3 h. Bizrah et al [14] also found that 87% of patients presented to the Moorfields Eye Hospital emergency department within 24 h, but they did not state the numbers of patients in more detailed time window (e.g., less than 3 h, within 3-6 h, within 6-12 h).…”
Section: Discussionsupporting
confidence: 93%
“…In these cases, it is difficult for the patient's visual function to recover. In nonmechanical ocular trauma due to the different injury mechanisms, the damage to the eye tissue is continuous, and patients are often blinded by long-term complications, such as corneal perforation, limbal stem cell deficiency, and secondary glaucoma [21].…”
Section: Discussionmentioning
confidence: 99%
“…Epithelial scraped mouse models were used to further investigate in vivo the benefits of hypothermically stored Ad-MSC bandages. It has been shown that Ad-MSCs can promote wound healing in various animal models using different approaches [ 38 , 81 , 82 ]. Our data show a reduction in corneal haze with an improvement in corneal healing shown by H&E staining.…”
Section: Discussionmentioning
confidence: 99%